Peranan Anggaran Biaya Produksi Sebagai Pengendalian Dalam Menunjang Efektifitas Projek Konsultasi Pendidikan Larispa Indonesia - Indah Ayu Lestari; Murni Dahlena Nasution (Forum Kerjasama Pendidikan Tinggi, 2022)
The aims of this study were (1) to describe how the preparation of the production cost budget for the education consulting project of Larispa Indonesia, (2) to describe how effective production cost control is at Larispa Indonesia, (3) to describe the role of the production cost budget in supporting the effectiveness of production cost control Larispa Indonesia Education Consulting Project. This study used a qualitative approach with a descriptive research type conducted at Larispa Indonesia. The types of data used are primary data and secondary data. Primary data includes interview data with informants, and secondary data in the form of data on the 2020-2022 Educational Consultation Project Budget. This study used a qualitative approach with a descriptive research type conducted at Larispa Indonesia. The types of data used are primary data and secondary data. Primary data includes interview data with informants, and secondary data in the form of data on the 2020-2022 Educational Consultation Project Budget. From the results of this study it is known that the production cost budget data and production cost realization starting in 2020-2022 show that the production cost budget realization shows a figure below 10%, this proves that the control carried out by Larispa has been effective. The production cost budget at Larispa Indonesia has played a significant role in the process of controlling production costs. Because the production cost budget that is applied has fulfilled the functions and objectives of the budget.